Refugees and conflict-affected people: Integrating displaced communities into food systems - Vos, Rob; Jackson, Julius; James, Sally; Sánchez, Marco V. (International Food Policy Research Institute, 2020)
Humanitarian interventions that have the greatest likelihood of success involve investing in local agrifood systems and including conflict-affected people in strategies for building, reviving, or strengthening these systems. KEY FINDINGS - More than half of all undernourished people live in countries affected by conflict. - Food insecurity and dispossession of agricultural assets can both trigger and result from civil strife. - Most conflict-affected countries are overwhelmingly rural, and rural populations are more vulnerable to climate shocks that often compound conflict situations. - Refugee host countries must often decide whether to focus responses on preparing affected populations to return home or helping them become economically self-reliant. - Integrating conflict-affected people into food systems— either in their new homes or the places they fled—can help them rebuild their lives.